2008
DOI: 10.1063/1.3009959
|View full text |Cite
|
Sign up to set email alerts
|

Growth evolution of surface nanowires and large anisotropy of conductivity on MgZnO/ZnO quantum wells based on M-nonpolar (10−10) ZnO

Abstract: Articles you may be interested inMgZnO/ZnO quantum well nanowire heterostructures with large confinement energies Self-organized surface nanowires were formed on M-nonpolar ͑10− 10͒ ZnO homoepitaxial layer surfaces. High-resolution transmittance electron microscopy showed that the surface nanowires possessed a flat plateau at the top and a side facet with constant step spacing at the atomic scale. In and ex situ observations of layer growth revealed that anisotropic islands appeared after growing two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…By rotating the samples it was observed that a majority of the nanorods in the present case makes an angle of approximately 301 with respect to the substrate normal. This value is similar to the reported inclination angle of ZnO nanorods grown on r-and m-plane sapphire by metal-organic vapor phase epitaxy and PLD method [18][19][20]. It should be noted, however, that the ZnO nanorods in the present study are inclined to only one side of the substrate normal.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…By rotating the samples it was observed that a majority of the nanorods in the present case makes an angle of approximately 301 with respect to the substrate normal. This value is similar to the reported inclination angle of ZnO nanorods grown on r-and m-plane sapphire by metal-organic vapor phase epitaxy and PLD method [18][19][20]. It should be noted, however, that the ZnO nanorods in the present study are inclined to only one side of the substrate normal.…”
Section: Resultssupporting
confidence: 89%
“…The common feature of nanorod tilting relative to the substrate normal was noticed in both cases of nanorods. Such offnormal ZnO nanorods/nanowires grown on a-plane GaN buffer layer, m-and r-sapphire substrates and MgO (1 0 0) substrate by vapor phase techniques have been reported [18][19][20]26]. By rotating the samples it was observed that a majority of the nanorods in the present case makes an angle of approximately 301 with respect to the substrate normal.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition to high surface energies on polar planes [24], the variation of adatom mobility and diffusion with different crystallographic directions [25] may facilitate the preference of Volmer-Weber growth mode on the c-plane. Pierce et al [14] and others [16,26] have shown monocrystalline deposition of ZnO on non-polar substrates and indicate the feasibility of step-flow growth on non-polar orientations. The utility of non-polar orientations have been favored for use in optoelectronic devices due to the reduction of internal electric fields, which lead to the quantum confined Stark effect (QCSE) and compromise quantum efficacies with increasing injected carrier density.…”
Section: Introductionmentioning
confidence: 97%
“…Astute deposition schemes [14] have been used to achieve contiguous epilayers on c-plane ZnO by MOVPE; the realization of Frank-van der Merwe growth mode has often been limited to physical deposition techniques such as pulsed laser deposition [15,16] and molecular beam epitaxy [17][18][19][20] or solution growth [21][22][23]. In addition to high surface energies on polar planes [24], the variation of adatom mobility and diffusion with different crystallographic directions [25] may facilitate the preference of Volmer-Weber growth mode on the c-plane.…”
Section: Introductionmentioning
confidence: 99%